Practice guidelines on the use of esophageal manometry – A GISMAD-SIGE-AIGO medical position statement. Issue 10 (October 2016) - Savarino, Edoardo; de Bortoli, Nicola; Bellini, Massimo; Galeazzi, Francesca; Ribolsi, Mentore; Salvador, Renato; Savarino, Vincenzo; Penagini, Roberto
Abstract: Patients with esophageal symptoms potentially associated to esophageal motor disorders such as dysphagia, chest pain, heartburn and regurgitation, represent one of the most frequent reasons for referral to gastroenterological evaluation. The utility of esophageal manometry in clinical practice is: (1) to accurately define esophageal motor function, (2) to identify abnormal motor function, and (3) to establish a treatment plan based on motor abnormalities. With this in mind, in the last decade, investigations and technical advances, with the introduction of high-resolution esophageal manometry, have enhanced our understanding and management of esophageal motility disorders. The following recommendations were developed to assist physicians in the appropriate use of esophageal manometry in modern patient care. They were discussed and approved after a comprehensive review of the medical literature pertaining to manometric techniques and their recent application. This position statement created under the auspices of the Gruppo Italiano di Studio per la Motilità dell'Apparato Digerente (GISMAD), Società Italiana di Gastroenterologia ed Endoscopia Digestiva (SIGE) and Associazione Italiana Gastroenterologi ed Endoscopisti Digestivi Ospedalieri (AIGO) is intended to help clinicians in applying manometric studies in the most fruitful manner within the context of their patients with esophageal symptoms.